Upaya Meningkatkan Hasil Belajar PAI dengan Menerapkan Pembelajaran Discovery Learning (DL) pada Siswa Kelas V SD Negeri 12 Cot Girek - Azizah (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
ABSTRACTOne of the efforts that can be made to create an active learning process is to use the right learning model. This research is "Efforts to Improve Pai's Learning Outcomes by Applying the Discovery Learning (DL) In Class V Students of State Elementary School 12 Cot Girek". The researcher chose this title because many students did not understand Islamic religious education well. The use of discovery learning models provides a meaningful learning experience so that the concepts they get will be embedded in students' memories longer and obtain good learning outcomes. This study uses a qualitative approach with the type of classroom action research. According to Arikunto (2007:16) "Classroom action research refers to a cycle system consisting of 4 components, namely: 1) planning, 2) implementation, 3) observation, 4) reflection. The subjects in this study were the fifth grade students of SD Negeri 12 Cot Girek, totaling 20 students consisting of 12 male students and 8 female students.